2002
DOI: 10.1128/aac.46.10.3164-3167.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the In Vitro Activity of the Glycylcycline Tigecycline (Formerly GAR-936) with Those of Tetracycline, Minocycline, and Doxycycline against Isolates of Nontuberculous Mycobacteria

Abstract: We compared the in vitro activity of the glycylcycline tigecycline (formerly GAR-936) with those of tetracycline, doxycycline, and minocycline by broth microdilution against 76 isolates belonging to seven species of rapidly growing mycobacteria (RGM) and 45 isolates belonging to five species of slowly growing nontuberculous mycobacteria (NTM). By using a resistance breakpoint of >4 g/ml for tigecycline and >8 g/ml for tetracycline, all RGM were highly susceptible to tigecycline, with inhibition of 50% of isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(129 citation statements)
references
References 23 publications
6
114
1
8
Order By: Relevance
“…Tigecycline (GAR-936) is a new semisynthetic glycylcycline (tetracycline analogue) and is effective against intra-abdominal, skin and soft-tissue infections caused by staphylococci, enterococci or streptococci, as well as most Enterobacteriaceae and anaerobic pathogens [29,52]. Tigecycline is effective against rapid-growing mycobacteria (Mycobacterium fortuitum, Mycobacterium chelonae and Mycobacterium abscessus) but showed no activity against more slow-growing mycobacteria (M. tuberculosis) [52,53].…”
Section: Tetracyclinesmentioning
confidence: 99%
“…Tigecycline (GAR-936) is a new semisynthetic glycylcycline (tetracycline analogue) and is effective against intra-abdominal, skin and soft-tissue infections caused by staphylococci, enterococci or streptococci, as well as most Enterobacteriaceae and anaerobic pathogens [29,52]. Tigecycline is effective against rapid-growing mycobacteria (Mycobacterium fortuitum, Mycobacterium chelonae and Mycobacterium abscessus) but showed no activity against more slow-growing mycobacteria (M. tuberculosis) [52,53].…”
Section: Tetracyclinesmentioning
confidence: 99%
“…Although combination therapies including amikacin and clarithromycin are generally used, the treatment of Mycobacterium abscessus can be very difficult due to development of high resistance against antituberculous drugs (9). Some studies reported the efficiency of tigecycline in the treatment of M. abscessus (10). In another study, patients with M. abscessus pulmonary disease who were treated with multi-drug antibiotic therapy and surgery or antibiotic therapy alone had similar clinical outcomes (11).…”
Section: Clinical Characteristics Of Nontuberculosismentioning
confidence: 87%
“…9 Tigesiklinin M. abscessus tedavisinde etkin olduğunu gösteren bazı araştırmalar bulunmaktadır. 29 Leber ve ark. tarafından gerçekleş-tirilen çok-değişkenli analizde, M. abscessus enfeksiyonu, intravenöz tedavi ve M. xenopi enfeksiyonunun, aylık tedavi maliyetlerinde artış ile yakından ilişkili olduğu gösterilmiştir.…”
Section: Discussionunclassified